Cast removable partial denture improving appearance and masticatory function - A case report (Update Dental College Journal, 2013)
Dentists are disappointed after delivery of cast removable partial dentures because their patient refuses or is unable to wear the denture and the treatment is therefore deemed unsuccessful. When so many patients do not comply with treatment, it is instructive to reflect on why and how the treatment is performed. Appropriate, comprehensive treatment planning should precede and eliciting the patient's chief complaint, as well as his or her expectations of treatment before treatment planning. The case presentation provides for the practitioner to discuss the patient's expectations and to outline both favourable and unfavourable short and long term outcomes. By providing this information, the practitioner ensures that the patient is fully informed before giving consent and that he or she understands the associated benefits and risks. DOI: http://dx.doi.org/10.3329/updcj.v1i1.13948 Update Dent. Coll. j: 2011; 1 (1): 14-17